Smartphone-Based Operating System Adoption Rate in Millennial Generation - Jose L.G Amparo (International Journal of Information Technology and Education, 2021)
The development of Android into a smartphone operating system is the most widely used in the world. The Android system is an option for companies that want a low-cost operating system. This study was conducted to analyze whether the Android Operating System Comparison Lollipop, Marshmallow, and Nougat versions in terms of performance and user satisfaction. The research was conducted using a questionnaire as a research instrument. The research questionnaire distributed consisted of 10 questions. Based on data processing, the results obtained are 9 The number of respondents who use the Android Operating System v5.0 (Lollipop) with a value of 30%, while the number of respondents who use the Android Operating System V6.0 (Marshmallow) there are 10 respondents with a percentage value of 33.3% and those who use the Operating System. Android v7.0 (Nougat) has 11 respondents with a percentage value of 37.7.